PENURUNAN INDUSTRI MANUFAKTUR TERHADAP TURUNNYA EKSPOR IMPOR - Iskandar, Audrya Randiva Aisyah; Subandi, Marcelin Diastiningsih; Pasaribu, Rapita Rani Br (Investama : Jurnal Ekonomi dan Bisnis, 2024)
The manufacturing industry is a processing industry, namely a business that processes or changes raw materials into finished goods or semi-finished goods that have added value, which is done mechanically with machines, or without using machines. The processing industry sector is very important for the economic development of a country because of its contribution to national economic development goals, especially in the formation of a large GDP and its ability to increase high value. The manufacturing industry sector again provided the highest contribution to achieving national export value in the January-April 2023 period. The manufacturing industry significantly influences a country's exports and imports. Contribution to the economy means that the manufacturing industry often becomes one of the main sectors in a country's economy. Export growth also affects the manufacturing industry which allows a country to produce products that can be sold to international markets. Dependence on Imports affecting manufacturing industries often relies on imports of raw materials, technology, or special equipment. Production efficiency that spurs progress in the manufacturing industry can increase production efficiency, which can reduce production costs and make products more competitive in the global market. Added value in manufacturing can add value to products by processing raw materials into finished goods. The manufacturing industry also creates significant employment opportunities, which can influence poverty rates and welfare levels in a country. High-quality manufactured products can build a country's positive reputation in international markets, enabling greater exports. The importance of the manufacturing industry in a country's economy and its impact on international trade makes it a very relevant topic ineconomic and trade policy.